QRIS usage dynamics in Banjarmasin: trust mediating perceived usefulness and perceived ease of use - Fitria, Firda Rizqika; Dairobi, Muhammad; Anisah, Hastin Umi (Manajemen dan Bisnis, 2024)
This study explores the pivotal role of trust in mediating the impact of perceived usefulness and ease of use on the adoption of QRIS (Quick Response Code Indonesian Standard) among the residents of Banjarmasin. Employing a purposive sampling method, the research gathered data from 353 QRIS users, predominantly women, across various districts and demographic backgrounds. The results of this research showed that both perceived usefulness and perceived ease of use strongly influence trust, which in turn significantly affects the usage decision. The research corroborates similar studies, emphasizing the necessity of enhancing system usability and trust to foster higher adoption rates. This study provides crucial insights for stakeholders aiming to optimize QRIS as a widely accepted payment platform in Banjarmasin, highlighting the importance of focusing on user-centric design and trust enhancement to drive technological adoption and usage.